Legal Analysis of Criminal Acts of Children and Women Against Sexual Violence in the Study of Criminal Sociology Perspective - Ritonga, Masdiansyah; Hakim, Abdul; Jannah, Maya (Enrichment: Journal of Multidisciplinary Research and Development, 2024)
Sexual violence against children and women is a pressing issue that impacts the safety and well-being of victims and society as a whole. This phenomenon is particularly concerning in va.rious regions, including South Labuhanbatu Regency, where multiple factors contribute to its occurrence. Understanding these factors and implementing effective measures to address them is crucial for creating a safer environment. The purpose of this study is to determine criminal acts against children and women for sexual violence in the study of criminal sociology perspective. This research uses a Juridical-Sociological legal approach. The results of the discussion show several factors that influence the occurrence of sexual violence against children in the South Labuhanbatu Regency, namely economic factors, individuals, social environment, family relationships or conflicts, and gender. In addition, the Labuhanbatu Resort police's efforts to minimize cases of sexual violence involve two main approaches: preventive action through socialization, legal counseling, and education and training targeting children and women, and repressive action with law enforcement against perpetrators of sexual violence by applicable legal provisions. The implication of this research is the importance of increasing preventive efforts through more intensive education and counseling for the community, as well as strengthening law enforcement against perpetrators of sexual violence. In addition, this research emphasizes the need for collaboration between various parties, including the government, legal institutions, and the community, to create a safer and more supportive environment for children and women.